The anatomy of evil - Stone, Michael H. (Prometheus Books, 2009)
Evil in peacetime -- Crimes of impulse : murders of jealousy and rage -- Other crimes of impulse : emphasis on antisocial persons -- Murder on purpose : the psychopathic schemers -- Spree and mass murder : evil by the numbers -- The psychopath hard at work -- Serial killers and torturers -- The family at its worst -- Science looks at evil -- Final thoughts